Evaluating the Financial Performance of PT Mitra Keluarga Karyasehat Tbk: Financial Ratio Analysis for 2022-2023 - Subagyo, Imam; Ramadhan, Yanuar; Sandrawati, Agnes; Kumala, Ratna Dewi; Andika, Dade (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This study aims to analyze the financial performance of PT Mitra Keluarga Karyasehat Tbk using various financial ratio analysis methods. The analysis was conducted on the company's financial statements for the period 2022 and 2023. The methods used include liquidity, activity, leverage, and profitability ratio analysis. The results showed that PT Mitra Keluarga Karyasehat Tbk experienced an increase in liquidity and a reduction in leverage but faced a decrease in operational efficiency and profitability. The Current Ratio increased from 3.82 in 2022 to 4.97 in 2023, and the Quick Ratio increased from 3.73 to 4.82. However, Receivable Turnover and Inventory Turnover decreased, indicating a decline in the efficiency of current asset management. The leverage ratio shows a decrease in dependence on debt, but the Interest Coverage Ratio decreased from 104.16 to 77.88, indicating a reduced ability to cover interest expenses. Profitability ratios declined, suggesting a need for improvement in cost management and revenue generation strategies. Overall, the company needs to focus on enhancing operational efficiency and cost management to improve future financial performance.